The effect of forage type on lamb carcass traits, meat quality and sensory traits - De Brito, Gerlane F. [UNESP]; McGrath, Shawn R.; Holman, Benjamin W. B.; Friend, Michael A.; Fowler, Stephanie M.; van de Ven, Remy J.; Hopkins, David L. (Elsevier B.V., 2016)
The aim of this study was to evaluate the effect of different forage-types on lamb carcass, meat quality and sensory attributes. Sixty-two, White Dorper lambs finished on bladder clover, brassica, chicory + arrowleaf clover, lucerne + phalaris or lucerne, were slaughtered at a commercial abattoir. At 24 h post-mortem, them. longissimus thoracis et lumborum (LL) was removed from the left side and sliced into three equal sub-samples, vacuum packaged and randomly assigned to ageing periods (5, 12 or 40 days) and the right side was aged for 5 days. The m. semimembranosus and m. adductor femoris were removed and, the former was then aged for 40 days. Lambs fed chicory + arrowleaf clover or lucerne had a higher dressing percentage and fat depth. Bladder clover gave the highest level of glycogen in the LL. No sensory or other meat quality trait differences were found between the treatments. In general, no treatments showed any unfavourable effect on the traits examined. Crown Copyright (C) 2016 Published by Elsevier Ltd. All rights reserved.
Keywords: Chicory; Grazing forages; Bladder; Colour; Glycogen; Brassica; Dressing percentage